Successful treatment of anti-NMDA receptor encephalitis with early teratoma removal and plasmapheresis: A case report. Issue 31 (August 2018) - Gomes Ferreira, Monica; Lapresa Alcalde, Victoria; García Sánchez, María Helena; Hernández Hernández, Lourdes; Doyague Sánchez, María José
Abstract: Rationale: This report describes a Successful treatment of anti-NMDA receptor encephalitis with early teratoma removal and plasmapheresis. Patient Concerns: We present a 31-year-old Caucasian nulliparous patient who was admitted as an emergency with general illness status accompanied by holocranial cephalalgia and fever. Diagnoses: The previous symptoms were followed by disorientation, persecutory delusion, incoherent language, and tonic-clonic seizure. Interventions: The patient was admitted in the intensive care unit (ICU) with Glasgow score 7. Outcomes: Most of complementary exams (brain CT, brain MRI, blood analysis, PCR for virus on CSF) were normal except CSF leucocytosis and hyperproteinorrhachia. An abdominopelvic ultrasound revealed a 5-cm solid-cystic tumor in the left adnexal region, suggestive of teratoma. At that stage, the possibility of autoimmune encephalitis was considered, and confirmed later. Lessons: This disease can only be successfully treated with fast surgical intervention and an early implementation of immunosuppressive therapies. The optimal timing of initiation and duration of therapeutic plasma exchange necessary to achieve good outcomes in patients with NMDAR remains unknown. This case report intends to increase awareness about the importance of early surgical treatment and early implementation of this potentially life-saving therapy and of continuing the treatment until complete remission of symptoms.